Relationship functioning and substance use in same-sex male couples. (1st August 2019) - Starks, Tyrel J.; Robles, Gabriel; Bosco, Stephen C.; Doyle, Kendell M.; Dellucci, Trey V.
Highlights: Relationship functioning predicted AUDIT scores in a sample of male couples. Relationship functioning predicted the use of miscellaneous recreational drugs. Relationship functioning may be a mechanism for drug use intervention. Abstract: Background: Research suggests that substance use among partnered sexual minority men will be inversely associated with the quality of dyadic functioning. We tested whether dimensions of relationship functioning implied within Couples Interdependence Theory (e.g., rewards, costs, barriers, alternatives, investment, and comparison to an ideal) predicted drug use and problematic alcohol use consistent with this hypothesis. Methods: This study utilized baseline data from a sample of 70 couples recruited in the New York City area. All participants were cis-gender male and 18 or older. In each couple, at least one partner reported recent drug use, at least one was aged 18 to 29, and at least one was HIV negative. Participants provided demographic information; completed measures of relationship functioning and problematic alcohol use; and reported recent (past 30 day) drug use. Results: Actor-partner interdependence models were calculated. The use of miscellaneous recreational drugs (excluding marijuana) was positively associated with participants' perception of rewards, costs, and barriers to leaving and negatively associated with comparisons to an ideal, alternatives, and investment. In addition, partner perceptions of rewards were positively associated with this outcome. AUDIT scores were negatively associated with comparison to an ideal; and positively associated with partner perceptions of alternatives. Relationship functioning was unrelated to marijuana use. Conclusions: These findings provide support for the hypothesis that relationship functioning and substance use are related. Couples Interdependence Theory implies such an assumption and it underlies many couples-based approaches to drug use intervention. These findings point to the potential utility of integrating relationship skill building into substance use interventions for partnered sexual minority men.